2021
DOI: 10.1021/acs.jpclett.1c02454
|View full text |Cite
|
Sign up to set email alerts
|

Topology-Mediated Enhanced Polaron Coherence in Covalent Organic Frameworks

Abstract: We employ the Holstein model for polarons to investigate the relationship among defects, topology, Coulomb trapping, and polaron delocalization in covalent organic frameworks (COFs). We find that intrasheet topological connectivity and π-column density can override disorder-induced deep traps and significantly enhance polaron migration by several orders of magnitude in good agreement with recent experimental observations. The combination of percolation networks and micropores makes trigonal COFs ideally suited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(29 citation statements)
references
References 62 publications
1
28
0
Order By: Relevance
“…The topology greatly influences the conductivity and magnetic properties of 2D conjugated COFs. For example, in contrast to the kagome, tetragonal, and hexagonal COFs, it has been reported that the trigonal counterparts are more advantageous for charge transport and that the Lieb lattice is promising in ferromagnetism . Interestingly, combining building blocks with C 2 and D 2 h symmetries can either render COFs with uniform rhombic pores or COFs with a kagome lattice comprising both triangular and hexagonal pores.…”
Section: Design and Synthesis Of 2d Conjugated Cofsmentioning
confidence: 99%
“…The topology greatly influences the conductivity and magnetic properties of 2D conjugated COFs. For example, in contrast to the kagome, tetragonal, and hexagonal COFs, it has been reported that the trigonal counterparts are more advantageous for charge transport and that the Lieb lattice is promising in ferromagnetism . Interestingly, combining building blocks with C 2 and D 2 h symmetries can either render COFs with uniform rhombic pores or COFs with a kagome lattice comprising both triangular and hexagonal pores.…”
Section: Design and Synthesis Of 2d Conjugated Cofsmentioning
confidence: 99%
“…Conjugated polymers, especially those with fully π-conjugated two-dimensional (2D) structures, exhibit an array of electronic structure characteristics, which make them attractive for applications in solar-to-chemical energy conversion. , Rational design and synthesis of conjugated polymers with ordered topological structures could extend π-delocalization over the entire framework, resulting in efficient charge transfer. In addition, recent theoretical calculations have also revealed that the charge transport properties of 2D conjugated polymer networks are highly dependent on the lattice symmetry. , For example, 2D conjugated polymers with the kagome lattice typically display flat or nearly flat bands around the Fermi energy. These flat bands are indicative of very high charge-carrier effective masses, which are not favorable for achieving high carrier mobilities.…”
Section: Perspective and Outlookmentioning
confidence: 99%
“…Building upon the 3D Holstein polaron model that was recently developed to investigate the effect of defects, domain size, chemical doping, and topology on the mid-IR photophysical signatures and charge transport properties of COFs, 216,217 future studies will go beyond a simple single chain analysis and focus on developing 3D vibronic exciton models for various COF topologies. Explicit inclusion of intra-and inter-framework electronic interactions, Frenkel and charge separated exciton states, and strong electron-phonon coupling on equal footing is necessary to investigate the spectral changes in both the UV-vis absorption and emission lineshapes of COFs.…”
Section: Application Of the Mhfmentioning
confidence: 99%
“…In this context, taking advantage of sparse matrix techniques and MPI parallelization on multinode clusters, we have shown that it is possible to extend the application of multiparticle modeling to large "vibronic" 3D systems, with negligible loss of accuracy. 216,217 The article is organized as follows: In Section 2 we briefly discuss the MHF. Section 3 highlights the photophysical signatures of Frenkel, charge-transfer, and Wannier-Mott excitons in organic (polymers and COFs) and hybrid (MOFs and perovskites) materials.…”
Section: Introductionmentioning
confidence: 99%